Stories for children - Wilde, Oscar, 1854-1900.; Lynch, P. J. (London : Hodder Children's Books, 2006)
A collection of six short children's stories by nineteenth-century Irish playwright, novelist, poet, and short story writer Oscar Wilde.
The selfish giant -- The nightingale and the rose -- The devoted friend -- The happy prince -- The remarkable rocket -- The young king.
"First published in 1990 by Simon and Schuster Young Books"--T.p. verso.
Cover title: Oscar Wilde : stories for children.
6.0
K-3
Keywords: Children's stories, English; Fairy tales -- England; Fairy tales; Fairy tales; Short stories